Peran Advokat Dalam Menjalakan Tugasnya Sebagai Penegak Hukum Yang Menjadi Kuasa Hukum Dalam Sistem Peradilan Pidana Berdasarkan Undang-Undang No. 18 Tahun 2003 Tentang Advokat - Ferro Stevani; Margo Hadipura (Jurnal Ilmiah Wahana Pendidikan, 2022)
Article 5 of Law No. 18 of the Republic of Indonesia of 2003 on Advocates provides for the presence of Advocates as enforcers. However, the actual shape and status of the role of the advocate as an enforcer is still unclear, especially with regard to its role as a supporting component in the realization of the criminal justice system, and therefore criminal enforcement in Indonesia is suboptimal. This study adopts normative legal research method or literature research, namely by analyzing the Law of the Republic of Indonesia No. 18 of 2003 on Defenders and the Law of the Republic of Indonesia No. 8 of 1981 on Criminal Procedure (KUHAP), as well as other laws and regulations and libraries material. Related to the role of the advocate in answering the question. The results of the study show that, in terms of form and location, there are 2 (two) roles of the defender as a law enforcement officer, namely (1) the role of the defender, that is, the form of providing legal aid to the offender under Article 54 of the Criminal Procedure Law . The Code, (2) the role of advocates for legal aid in the form of legal aid provided to victims under the Code of Criminal Procedure. outside the criminal procedure law. Hope it can be an input for Indonesian law enforcement and judicial enforcement officers.